PGS analysis of over 100,000 blastocysts using high resolution next generation sequencing - Sawarkar, SS; Large, M; Fragouli, E; Wells, D; Escudero, T; Ribustello, L; Blazek, J; Munne, S (Elsevier, 2017)
To determine the types and frequency of abnormalities in human blastocyst detected by high resolution next generation sequencing (hr-NGS) stratified by age and laboratory.